(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2023)
In this paper I use the operators Dmβ,η(η, φ)f, Sm(d, β, η) and Cm(d, β, η).To establish |a3−μa22 | -functional inequalities for the Fekete-Szeg ̈o problem. That’s my main result.